Increasing the Level of Professional Competence Using a Virtual Educational Environment - V. A. Nemtinov; A. B. Borisenko; V. V. Morozov; Yu. V. Nemtinova (Moscow Polytechnic University, 2021)
The article addresses the issues of creating a virtual educational environment using special equipment. The 3DVista Virtual Tour program was chosen as the development environment for the virtual tour, using features related to e-Learning and automatic integration with LMS Moodle. The virtual space of the created educational environment provides an opportunity for the existence of various forms of educational communication, based on the capabilities of modern teaching tools and modern information and communication technologies, allows you to provide conditions for improving the quality of education, exchanging of views, and mutual consultation. The use of web-quest technology will allow young people to shape their common understanding of the profession, realize the demands placed on professionals in this sphere, will contribute to identify their personal and professional interests and aptitudes, and will also help schoolchildren and students to make independently and consciously their professional choice This technology fosters the development of communication skills and a more intensive exchange of information in the process of learning or mastering new academic material. All this ensures an increase in the level of professional competence of schoolchildren and students.